Penyuluhan Kesehatan Tentang Perilaku Hidup Bersih dan Sehat (PHBS) Pada Penjamah Makanan Di Kantin Lingkungan Universitas Mataram: Health Education about Clean and Healthy Living Behavior for Food Handlers in the Canteen at the University of Mataram - Hasbi, Nurmi; Candrawati, Tania Happy; Wijaya, Ni Wayan Puspa (Universitas Mataram, 2024)
Clean and Healthy Living Behavior (PHBS) is a good practice that must be implemented by everyone in maintaining personal and environmental cleanliness. This service activity aims to provide health education about good and correct PHBS to food handlers in the canteen at the University of Mataram. The service method used is interactive discussion and question and answer. Service members consist of lecturers and students from the medical education study program, Faculty of Medicine and Health Sciences, Mataram University. The service participants consisted of 10 food handlers from 7 canteens including the UNRAM food court, the Faculty of Medicine and Health Sciences canteen, the UPT Language Center canteen, the Faculty of Mathematics and Natural Sciences canteen, the Faculty of Business Economics canteen, the International Relations or Law canteen and the Faculty canteen Education Science Teacher. The questionnaire showed that as many as 90% of food handlers did not wear masks, 80% did not use gloves, 70% did not use aprons and 100% of food handlers did not know the practice of the 6 steps for washing hands. It is hoped that this service activity can educate food handlers. This is because the quality of food is not only seen from nutrition and appearance, but must be free from any potential infectious agents that can occur or are known as food borne diseases. The service participants felt satisfied and understood the PHBS steps.